MUTU PELAYANAN STANDAR PELAYANAN MINIMAL (SPM) PENDAFTARAN PASIEN DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN (TPPRJ) PUSKESMAS NGALIYAN KOTA SEMARANG - Agiwahyuanto, Faik; Hari Noegroho, Ferdiansyah (MEDIA ILMU KESEHATAN, 2019)
Background: Minimum Service Standards (SPM) in outpatient services at the Ngaliyan Community Health Center reads the standard time to serve old patients ie 5 minutes while patients are only 7 minutes. Based on the initial survey of 10 outpatients in the Ngaliyan Health Center divided into 5 old patients and 5 new patients, it was found that on average the officers served the old patients ie 18 minutes 17 seconds and the new patients were 18 minutes 32 seconds. Objective: This study aims to analyze the service quality minimum (SPM) of TPPRJ inpatient registration at the Ngaliyan Health Center Semarang City. Methods: This study used an observational analytic research design with cross-sectional approach at Ngaliyan Public Health Center Semarang City. The sampling technique used purposive sampling with total sample are 20 respondents. Analysis data using univariate with percentage. Result: The results showed that in 1st stage average time service old patients is 6 minutes 13 seconds and new patients is 12 minutes 6 seconds. In 2nd stage average time service old patients is 11 minutes 3 seconds and new patients is 12 minutes 6 seconds. Conclusion: SPM service quality of inpatients registration influenced by inpatient waiting time.